Color outside the lines: How does amoral management influence employees’ creative unethicality? - Lei Ren; Yan Liu; Abdul Waheed Siyal; Xiaobin Zhang; Tianxing Pu (PLoS ONE, 2026)
Existing research has confirmed that amoral management can induce employees to engage in unethical behavior. However, its influence on a specific form of misconduct that involves creativity—namely, creative unethicality—remains unclear. Based on social information processing theory, this study constructs a theoretical model examining the influence of amoral management on employees’ creative unethicality. Through a three-stage investigation of 249 R&D employees from three intelligent manufacturing companies in eastern China, the results reveal that amoral management positively influences employee moral decoupling. Moral decoupling leads to creative unethicality under high job creativity requirements. Job creativity requirements moderates the indirect effect among amoral management, moral decoupling, and creative unethicality. Specifically, when jobs require high creativity, amoral management positively influences moral decoupling, thereby inducing creative unethicality. This study combines amoral management and creative unethicality, broadening the understanding of creative unethicality origins from the viewpoint of leaders’ moral conduct. It also provides empirical insights for organizations to manage creative unethicality through job stressors and leadership development.